2012
DOI: 10.1136/oemed-2012-101155
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer associated with six types of chlorinated solvents: results from two case–control studies in Montreal, Canada: Table 1

Abstract: There were suggestive, albeit inconsistent, indications that exposure to perchloroethylene and carbon tetrachloride may increase the risk of lung cancer. Results for other solvents were compatible with absence of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
11
1
2
Order By: Relevance
“…Finally, studies of the health effects of PCE published since the U.S. EPA’s assessment continue to report associations with neurological outcomes, including studies of illicit drug use (Aschengrau et al 2011); mental illness (Aschengrau et al 2012); visual effects (Getz et al 2012); visuospatial functioning, learning and memory, motor, attention, and mood (Janulewicz et al 2012); and Parkinson disease (Goldman et al 2012). Similarly, recent analyses of PCE exposure and cancer continue to add support for human tumor sites identified in the Toxicological Review (Christensen et al 2013; Lipworth et al 2011; Ruder et al 2013; Vizcaya et al 2013; Vlaanderen et al 2013; 2014). …”
Section: Discussionmentioning
confidence: 89%
“…Finally, studies of the health effects of PCE published since the U.S. EPA’s assessment continue to report associations with neurological outcomes, including studies of illicit drug use (Aschengrau et al 2011); mental illness (Aschengrau et al 2012); visual effects (Getz et al 2012); visuospatial functioning, learning and memory, motor, attention, and mood (Janulewicz et al 2012); and Parkinson disease (Goldman et al 2012). Similarly, recent analyses of PCE exposure and cancer continue to add support for human tumor sites identified in the Toxicological Review (Christensen et al 2013; Lipworth et al 2011; Ruder et al 2013; Vizcaya et al 2013; Vlaanderen et al 2013; 2014). …”
Section: Discussionmentioning
confidence: 89%
“…The lung was not considered a likely target organ 32. Interestingly, one study recently published also suggested an association with lung cancer risk for ‘substantial’ levels of exposure to PCE, although the number of subjects was small 9. Because PCE is used extensively in the dry-cleaning sector, several cohort studies were conducted on subjects employed in dry-cleaning as a proxy for PCE exposure,8 33 34 and reported a moderately increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, results from relatively large case-control studies on chlorinated solvents (including TCE) and lung cancer risk have been reported [20,21]. Vizcaya et al pooled data from two Canadian casecontrol studies (totaling 2016 cases and 2001 controls) conducted in 1980-1986 and 1995-2001, respectively [21]. Exposure to 6 chlorinated solvents was evaluated by an expert assessment.…”
Section: Occupational Tce Exposure and Lung Cancermentioning
confidence: 99%